2012
DOI: 10.1371/journal.pone.0031139
|View full text |Cite
|
Sign up to set email alerts
|

High Diversity of Cryptosporidium Subgenotypes Identified in Malaysian HIV/AIDS Individuals Targeting gp60 Gene

Abstract: BackgroundCurrently, there is a lack of vital information in the genetic makeup of Cryptosporidium especially in developing countries. The present study aimed at determining the genotypes and subgenotypes of Cryptosporidium in hospitalized Malaysian human immunodeficiency virus (HIV) positive patients.Methodology/Principal FindingsIn this study, 346 faecal samples collected from Malaysian HIV positive patients were genetically analysed via PCR targeting the 60 kDa glycoprotein (gp60) gene. Eighteen (5.2% of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 52 publications
3
33
1
3
Order By: Relevance
“…The C. parvum IIaA13G1R1subtype detected in this study was previously reported in immunocompetent humans, HIV/AIDS patients, and domestic animals in Malaysia (4). A single case of human cryptosporidiosis caused by C. tyzzeri (incorrectly reported as the C. parvum IIf family, A6 subtype) was reported previously in a Kuwaiti child (5); however, the source of the infection was not identified.…”
supporting
confidence: 46%
“…The C. parvum IIaA13G1R1subtype detected in this study was previously reported in immunocompetent humans, HIV/AIDS patients, and domestic animals in Malaysia (4). A single case of human cryptosporidiosis caused by C. tyzzeri (incorrectly reported as the C. parvum IIf family, A6 subtype) was reported previously in a Kuwaiti child (5); however, the source of the infection was not identified.…”
supporting
confidence: 46%
“…Previously, the C. parvum subtype IIdA15G1 has been detected in cattle, sheep and goats in Iran, Malaysia, and Spain [34][35][36][37]. It has also been found in humans from the Netherlands, Australia, Iran, Malaysia, and India [37][38][39][40][41]. The IIdA15G1 subtype identified in this study was unlikely to have arrived via Uruguay or the United States because the C. parvum IId subtype family has never been found in the Americas [13].…”
Section: Findings and Discussionmentioning
confidence: 47%
“…This uncommon subtype has been found in calves in Turkey [25], Canada [26], Belgium [12], and the Netherlands [28], and in people with HIV/AIDS in Malaysia [16] and in the United States [28]. …”
Section: Discussionmentioning
confidence: 99%